Aleister Crowley and the temptation of politics - Pasi, Marco 1968- (Durham Acumen, 2014)
Aleister Crowley (1875-1947) is one of the most famous and significant authors in the history of western esotericism. Crowley has been long ignored by scholars of religion whilst the stories of magical and sexual practice which circulate about him continue to attract popular interest. ""Aleister Crowley and the Temptation of Politics"" looks at the man behind the myth - by setting him firmly within the politics of his time - and the development of his ideas through his extensive and extraordinarily varied writings. Crowley was a rationalist, sympathetic to the values of the Enlightenment, but
Cover; Half Title; Title Page; Copyright Page; Dedication; Table of Contents; Foreword; Acknowledgements; Abbreviations; Introduction; 1. An unspeakable life; 2. Magical politics; 3. Dangerous liaisons; 4. The Mouth of Hell; 5. Counter-initiation and conspiracy; Conclusion; Appendix 1: Some additional remarks on Julius Evola and Aleister Crowley; Appendix 2: Key documents; Notes; Bibliography; Index
Includes bibliographical references and index
Online-Ausg.
Keywords: Crowley, Aleister -- 1875-1947; Occultists -- Great Britain -- Biography; Electronic books